Liber amicorum : gouverneur Richard Declerck. - Baekelmans, Lode; Bal, Nic; Becu, Omer (Antwerpen : Ontwikkeling)
Deze publicatie bevat volgend lied
Pauvre Rutebeuf
Bibliotheek Hein PicardArchief Jef Dyck
Nederlands
Monografie
Keywords: Declerck, Richard; liederen